Anesthesia for bone replacement surgery - Sunil Singh; Shri Prakash Singh; Jitendra K Agarwal (Wolters Kluwer Medknow Publications, 2012)
Advances in clinical medicine, improved understanding of pathophysiology, and the extensive application of medical technology have projected hitherto high risk and poor outcome surgical procedures into the category of routine and relatively good outcome surgeries. Bone replacement surgery is one amongst these and is wrought with a multitude of perioperative complexities. An understanding of these goes a long way in assisting in the final outcome for the patient. Here we present a review of the literature covering various issues involved during the different stages of the perioperative period.